WATESNEGORO VILLAGE GOVERNMENT STRATEGY IN DEVELOPING TOURISM AT SUMBER GADUNG - Ahmad Riyadh Umar Balamar (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
Tourism development is an effort to improve, advance, and improve tourist facilities and services needed by the community. This research aims to analyze and explain the Strategy of the Watesnegoro Village Government in Developing Gadung Source Tourism. The basic concept used in this research is the theory of strategy according to James Brian Quinn including goals, policies, and programs. This qualitative research uses a purposive sampling technique. Data were collected using interviews, observation, and documentation. Data analysis used interactive Miles, Huberman, and Saldana. The results show that the objectives of tourism development in Watesnegoro Village are to increase the number of tourist visits, improve the community's economy, overcome unemployment, and preserve the environment. Policies in the development carried out by the village government are by making improvements and providing infrastructure, car free day activities, and gymnastics with tourists and including the role of youth organizations as tourism managers. The tourism potential development program is the utilization of promotional platforms including the creation of mass media, websites, and social media accounts (Instagram and Facebook) in disseminating Gadung sources and carrying out cooperation with the Sidoarjo Regency Youth, Sports, Culture and Tourism Office